2014
DOI: 10.1002/pros.22786
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of intraductal carcinoma of the prostate in radical prostatectomy specimens

Abstract: IDC-P in RP specimens was an independent risk factor for PFS and CSS and could predict clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 32 publications
(60 reference statements)
6
157
2
2
Order By: Relevance
“…5 Only one group reported that intraductal carcinoma of the prostate was an important adverse pathological parameter that could predict disease progression in metastatic 9,24 however, their results relied on univariate analysis. We showed that the incidence of intraductal carcinoma of the prostate was 36.3% in needle biopsies and 50.5% in radical prostatectomy specimens of high-risk prostate cancer patients, 6 and that the incidence rose to 67% in patients with distant metastasis at initial diagnosis. Visceral metastasis, performance status, pain, and hemoglobin and alkaline phosphatase levels were proposed as prognostic parameters for overall survival in the TAX327 study.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…5 Only one group reported that intraductal carcinoma of the prostate was an important adverse pathological parameter that could predict disease progression in metastatic 9,24 however, their results relied on univariate analysis. We showed that the incidence of intraductal carcinoma of the prostate was 36.3% in needle biopsies and 50.5% in radical prostatectomy specimens of high-risk prostate cancer patients, 6 and that the incidence rose to 67% in patients with distant metastasis at initial diagnosis. Visceral metastasis, performance status, pain, and hemoglobin and alkaline phosphatase levels were proposed as prognostic parameters for overall survival in the TAX327 study.…”
Section: Discussionmentioning
confidence: 84%
“…The median serum PSA was 328 ng/ml (range 4.18-10 992 ng/ml). The median-submitted number of cores was six (mean 7.3, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and the median number of cancer-positive cores was six (mean 5.8, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Intraductal carcinoma of the prostate was detected in 100 (67%) patients, six with PSA levels o 20 ng/ml and the remaining 94 with PSA levels 420 ng/ml.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations